Signos da vorazcidade: a comunicação do grotesco em Rubem Fonseca - Santos, Nelma Aronia (2012)
The years in which the works of Rubem Fonseca initially arise, 1963, and consolidate themselves 1970s coincide with a social, political and economical context of major transformation and social turbulence, such as: the installation of social barbarism and the regime of military dictatorship, and the advent and proliferation of mass communication media. Accordingly, our goal is to investigate the procedures of literary creation that dialogue with this context, within the short stories of Rubem Fonseca.